Reporting Marine Microplastics Data: the Need for a Standardized Protocol - Pauna, Valentina H.; Buonocore, Elvira; Renzi, Monia; Russo, Giovanni Fulvio; Franzese, Pier Paolo (Journal of Environmental Accounting and Management, 2026)
Marine microplastics have become an issue of great concern at the global level. The attention towards the issue of marine microplastics, highly recognized by international policy and scientific research, has increased considerably over the last decades. At the European level, several initiatives have been promoted addressing the reduction of plastic pollution as a high priority target, among which the Marine Strategy Framework Objective (D10) and the European Strategy for Plastics in a Circular Economy. In addition, researchers have explored many strategies to optimize the detection and monitoring of microplastics in sediments, seawater, and organisms and to effectively demonstrate their potential ecological harm. However, since pollution dynamics, the functioning of natural ecosystems, and their relationships are very complex, there still lacks a comprehensive understanding of the impacts of microplastics on marine ecosystems. This lack of knowledge may impact the effectiveness of decision-making processes in terms of plastic reduction and waste management. In this study, we present the results of a literature review which focuses on particularly impactful marine microplastic methodological and analytical articles from 2004 to 2017 to identify possible gaps or inconsistencies in the reported data. Based on this review, a framework for a general reporting protocol (GRP) is outlined to encourage increased collaborative research efforts to harmonize the reporting of microplastics data in scientific studies. The proposed GRP outline could be useful in addressing data needs for effective ecological risk assessment.